Workshop Penggunaan Aplikasi Publish or Perish (POP) dalam Mencari Referensi Jurnal pada Mahasiswa Universitas Palangka Raya - Putri, Windy Utami; Oktaria, Merisa; Oktobery, Revnussa (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
This community service aims to enhance the capabilities of students at the University of Palangka Raya in using the Publish or Perish (POP) application as a tool for searching and analyzing journal references. In the midst of rapid advancements in science, students need to be equipped with adequate skills to produce high-quality scientific work. The training was conducted at the Red and White building of the University of Palangka Raya and was attended by 43 participants. The methods used in the training included material presentation, practical exercises, and discussions, allowing participants to apply the knowledge gained in a practical manner. Evaluation results indicate a significant improvement in students' skills and understanding of the use of the POP application, which is expected to positively impact the quality of research and scientific publications in the academic environment Keywords : publish or perish, Student, Scientific references